Impact of Tourism on the Economy of Rwanda: Tourism Collective Consumption Multilier Effects - Odunga , Pius (African Journal of Education,Science and Technology (AJEST), 2019)
The primary objective of this study was to evaluate the economic impact of tourism collective consumption by the government for the year 2013/2014. The input-output/SAM models were used to estimate the impacts and effects. Data for analysis was sourced from EORA multi-region input-output table (MRIO) database. All impacts have a starting point in the economy, defined as the direct effect. The direct effect sets off iterations of indirect (inter-industry production) and induced (household purchases) spending. There are several different types of multipliers depending on the secondary effects included and the measure of economic activity used. The common multipliers computed were associated with output, income, value addition and employment in the economy. Multipliers were decomposed into their associated effects: initial, production and consumption effects. Tourism collective consumption of US$ 9 million created 79 thousand jobs, generated $4.7 million labour income, and added $11 million to total value in the economy and $23 million to total output. This shows the extent to which government expenditure on tourism collective services can stimulate the economy in terms of employment creation, value addition, income generation and output production. However, ways of apportioning public shared services to a particular sector in the economy are still inconclusive. This study could be the first to assess the economic impacts of tourism collective consumption. Future studies may re-estimate the multipliers by adopting Computable General Equilibrium (CGE) models and more advanced statistical methods of apportioning shared collective services to a particular sector of the economy.